Criminal Liability Of Perpetrators Of Assault Resulting In Serious Injury - Pimpin Satria Sihaloho; Fitria Ramadhani Siregar; Abdul Razak Nasution (Fakultas Hukum Dehasen, 2026)
In the Indonesian Criminal Code (KUHP), assault is classified as a criminal act directed against a person’s body, causing pain, injury, or impairment of health. Article 351 paragraph (2) KUHP regulates assault resulting in serious injury, punishable by imprisonment for up to five years. Any person who suffers pain, injury, or physical loss as a result of such conduct is regarded as a victim and is entitled to legal protection. Legal protection for victims of assault resulting in serious injury is essential to ensure the fulfilment of their rights, to provide a sense of security, and to guarantee adequate support, including proper legal assistance. This study is a normative juridical legal research which aims to examine the criminal law provisions and forms of legal protection for victims of assault resulting in serious injury, by focusing on statutory regulations, legal principles, and relevant legal doctrines. The method of analysis used is deductive reasoning, with data collected through library research on legislation, legal literature, and court decisions. The results of the study show that the Public Prosecutor charged the defendant primarily under Article 351 paragraph (2) KUHP, and the panel of judges in its decision accepted the primary charge, imposed a term of imprisonment on the defendant, and ordered the defendant to compensate the victim’s medical expenses. This decision reflects that law enforcement is directed not only at punishing the offender, but also at accommodating the protection and recovery of victims of assault resulting in serious injury.